Organizational culture and its relationship to job satisfaction among secondary school teachers in Daraj Municipality: A field study (Comprehensive Journal of Science, 2026)
The research problem is centered on the main question regarding the nature of the relationship between the prevailing organizational culture and job satisfaction among secondary education teachers in the Municipality of Darj, and whether there are differences in this relationship attributable to personal variables (gender, age, years of experience).The research aimed to identify the features of the prevailing organizational culture, the reality of organizational communication and systems/policies, the level of job satisfaction among teachers, and statistical differences between variables, in addition to measuring the relationship between organizational culture and job satisfaction.The study followed the descriptive analytical approach and was applied to a purposive sample of (39) male and female teachers from secondary education schools in the Municipality of Darj, selected from the study population of (200) teachers. A questionnaire was used as the primary tool for data collection, encompassing three axes: organizational culture, organizational communication and systems/policies, and job satisfaction.The most important findings of the researcher were as follows:The prevailing organizational culture enjoys a high level, as management is keen to promote ethical values, justice, and encourage teamwork.The level of organizational communication and systems/policies was high, with clarity of communication channels and institutional policies.The level of job satisfaction among teachers was high, especially concerning the feeling of the importance of their role and satisfaction with tasks.There are no statistically significant differences in the study axes attributed to the variables of gender and age.There are statistically significant differences attributed to the variable of years of experience between the categories (less than 5 years) and (more than 10 years).There is a weak, statistically significant positive correlation between organizational culture and job satisfaction at the level (0.05).Key Recommendations: Strengthening the positive organizational culture, paying attention to material and moral incentives, and providing the necessary capabilities to make the work environment more comfortable and motivating for teachers